1993
DOI: 10.1002/star.19930450508
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Structure of Aqueous Solutions of Hydroxypropyl‐beta‐Cyclodextrin

Abstract: Molecules of hydroxypropyl‐beta‐cyclodextrin (HPBCD) in aqueous solution interact with each other via hydrogen bonds. Especially for concentrations beyond 50% (w/w), a strong increase in viscosity and a considerable decrease of freezable water can be determined. The addition of substances which are able to break the water structure (urea, KSCN) reduces these effects remarkably. The formation of inclusion compounds with urea could not be detected. Endothermic phase transformations confirm the presence of liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 12 publications
9
28
0
Order By: Relevance
“…A similar observation was found for γ-CD (10% m/v) solutions [45], at physiological pH. In both works, the self-aggregation of CD monomers is justified by intermolecular H-bonding interactions promoted by the hydrophilic rims [44,45].…”
Section: Controversial Experimental Evidencesupporting
confidence: 80%
See 1 more Smart Citation
“…A similar observation was found for γ-CD (10% m/v) solutions [45], at physiological pH. In both works, the self-aggregation of CD monomers is justified by intermolecular H-bonding interactions promoted by the hydrophilic rims [44,45].…”
Section: Controversial Experimental Evidencesupporting
confidence: 80%
“…These authors have also pointed out that such aggregates are acting as "structure making" [43] by tightening water-water hydrogen bonding. Ten years later, Häusler and Müller-Goymann [44] have observed that at concentrations above 50% (w/w), hydroxypropyl (HP)-β-CD self-aggregates, leading to an increase in the solution viscosity. They also found that the addition of chaotropic solutes (e.g., urea and NaCl) tends to decrease the viscosity of solutions as a consequence of CD disaggregation.…”
Section: Controversial Experimental Evidencementioning
confidence: 99%
“…It is known from the literature 85 that these 'barrels' have an exterior which is covered by OH-groups while the interior cavity is quite hydrophopic, characterized by CH 2 groups. Due to the difficulties involved in the direct investigation (as already mentioned previously) the true solution structure of cyclodextrins in solution was still a matter of discussion 86,87 despite their high technical relevance.…”
Section: Cyclodextrins As Templatesmentioning
confidence: 99%
“…In order to apply the DLS technique to the investigation on cyclodextrin nanotubes, it is necessary to ascertain the self-aggregation phenomenon of cyclodextrin itself. Actually, the existing state of cyclodextrin in pure water still remains controvertible to some extent [27,28]. Recently, the self-aggregation of cyclodextrins and inclusion complexes between cyclodextrins and guest molecules has been investigated through DLS [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%